Modelling of Thin Films Hardness Measured by a Spherical Indenter - Boudilmi, A.; Loucif, K. (Металлофизика и новейшие технологии, 2018)
In this theoretical contribution, we chose to use an indenter having a spherical geometrical form, which we used to model the surfaces mixture to separate the contributions of substrate and film in the composite covered material hardness. We have considered the coefficients α, β of the model as ratios of the projections of the imprints at the horizontal plans (disks surfaces). We prove that the film hardness of monolayer coating is dependent on the composite and substrate hardness, the geometrical form of the indenter, and the film thickness.